2018
DOI: 10.1515/chem-2018-0125
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace fluoroquinolones in water solutions and in medicinal preparations by conventional and synchronous fluorescence spectrometry

Abstract: Simple, rapid and sensitive and synchronous fluorescence spectrometry (SFS) were developed for determination the fluoroquinolones of ciprofloxacin (CIP), norfloxacin (NOR) and enrofloxacin (ENR) separately in water solutions and in medicinal preparations. The optimized wavelength intervals between the emission and excitation wavelengths were 170 nm, 160 nm and 170 nm for CIP, NOR and ENR, respectively. The different experimental parameters affecting the synchronous fluorescence intensities of the three fluoroq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Linear range (μg·mL − 1 ) Detection limit (μg·mL − 1 ) Spectrofluorometric [65] 0.02-2.2 0.006-0.016 HPLC-UV [89] 0.15 to 5 0.04-0.08 HPLC [57] 0.003-1.3 0.001 HPLC-fluorescence [90] 0.005-0.1 0.0005-0.005 Capillary electrophoresis [83] 5-20 1.1 and 2.4 Chemiluminescence [77] 1.98 × 10 − 9 0.003-7 HPLC-PDA [91] 0.1-10 0.03 Spectrophotometric [72] 0.5-25 0.084 HPLC [92] 0.0005-1 0.00007 is method 0.25-20 0.035-0.093 International Journal of Analytical Chemistry substances on the proposed method for the determination of ciprofloxacin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear range (μg·mL − 1 ) Detection limit (μg·mL − 1 ) Spectrofluorometric [65] 0.02-2.2 0.006-0.016 HPLC-UV [89] 0.15 to 5 0.04-0.08 HPLC [57] 0.003-1.3 0.001 HPLC-fluorescence [90] 0.005-0.1 0.0005-0.005 Capillary electrophoresis [83] 5-20 1.1 and 2.4 Chemiluminescence [77] 1.98 × 10 − 9 0.003-7 HPLC-PDA [91] 0.1-10 0.03 Spectrophotometric [72] 0.5-25 0.084 HPLC [92] 0.0005-1 0.00007 is method 0.25-20 0.035-0.093 International Journal of Analytical Chemistry substances on the proposed method for the determination of ciprofloxacin.…”
Section: Methodsmentioning
confidence: 99%
“…Fluoroquinolones are among the most important antibacterial agents which were developed in the 80s and are now widely used in medicine and veterinary medicine [49]. erefore, several analytical procedure has been reported for determination of fluoroquinolones including high-performance liquid chromatography (HPLC) [50][51][52][53][54][55][56][57][58][59][60][61][62], spectrophotometry [63], fluorimetry [64][65][66][67][68][69][70][71][72][73], flow-injection based on chemiluminescence [74][75][76], chemiluminescence [77,78], terbium-sensitized luminescence [79], solid-phase spectrofluorimetry [80,81], capillary electrophoresis [82,83], convenient magnetic solid-phase extraction procedure coupled with capillary electrophoresis [84], solid-phase microextraction coupled with liquid chromatography-tandem mass spectrometry [85], liquid-liquid microextraction [86], polarography [87], and colorimetry [88] But, there is no report for application of PAT or PAC for online monitoring of fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…Ciprofloxacin (CF) is one of the most widely used antibiotics in the FQ group: used in human, agricultural, and veterinary practices. Because of the indiscriminate use of the drug against common infectious symptoms, CF has been widely detected in surface water and groundwater. ,, This is mostly due to the release of untreated or partially treated pharmaceutical effluents directly into the waterbodies. The incomplete metabolism of the drug by target cells also contributes to the presence of antibiotic residues in untreated sewage waste …”
Section: Introductionmentioning
confidence: 99%
“…Thus, most of these drugs have led to a significant increase into the environment as prototypes or active metabolites in recent years. In addition, some experimental results demonstrated that these FQs might change the structures of microorganisms in the soil and aquatic environment, which eventually lead to drug resistant bacteria [19,20].…”
Section: Introductionmentioning
confidence: 99%